2012
DOI: 10.1073/pnas.1200196109
|View full text |Cite
|
Sign up to set email alerts
|

Number sense across the lifespan as revealed by a massive Internet-based sample

Abstract: It has been difficult to determine how cognitive systems change over the grand time scale of an entire life, as few cognitive systems are well enough understood; observable in infants, adolescents, and adults; and simple enough to measure to empower comparisons across vastly different ages. Here we address this challenge with data from more than 10,000 participants ranging from 11 to 85 years of age and investigate the precision of basic numerical intuitions and their relation to students' performance in schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
451
7
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 443 publications
(505 citation statements)
references
References 37 publications
(45 reference statements)
40
451
7
7
Order By: Relevance
“…While some of these researchers have indexed ANS acuity using Weber fractions (e.g. Castronovo & Gobel, 2012;Halberda et al, , 2012Inglis et al, 2011;Libertus et al, 2012;Lyons & Beilock, 2011;Piazza et al, 2010;Price et al, 2012;Sasanguie et al, 2012), others have used NREs (e.g., Bugden et al, 2012;Holloway & Ansari, 2009;Lourenco et al, 2012;Merkley & Ansari, 2010;Price et al, 2012), and others accuracy (e.g. Fuhs & McNeil, 2013;Nys et al, 2013;Wei et al, 2012).…”
Section: Price Et Al (2012) Calculated Immediate Test-retest Reliabimentioning
confidence: 99%
See 1 more Smart Citation
“…While some of these researchers have indexed ANS acuity using Weber fractions (e.g. Castronovo & Gobel, 2012;Halberda et al, , 2012Inglis et al, 2011;Libertus et al, 2012;Lyons & Beilock, 2011;Piazza et al, 2010;Price et al, 2012;Sasanguie et al, 2012), others have used NREs (e.g., Bugden et al, 2012;Holloway & Ansari, 2009;Lourenco et al, 2012;Merkley & Ansari, 2010;Price et al, 2012), and others accuracy (e.g. Fuhs & McNeil, 2013;Nys et al, 2013;Wei et al, 2012).…”
Section: Price Et Al (2012) Calculated Immediate Test-retest Reliabimentioning
confidence: 99%
“…Bonny & Lourenco, 2013;Castronovo & Göbel, 2012;Halberda, Ly, Willmer, Naiman, & Germine, 2012;Inglis et al, 2011;Libertus et al, 2011Libertus et al, , 2012Lyons & Beilock, 2011;Mazzocco et al, 2011a;Piazza et al, 2010;Price et al, 2012;Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013). It makes the INDEXING THE APPROXIMATE NUMBER SYSTEM 5 theoretical assumption that the ANS operates according to the Weber-Fechner law (e.g.…”
mentioning
confidence: 99%
“…The Approximate Number System (ANS) is believed to be a cognitive system that underlies this sense of number (Dehaene, 1997). Many researchers have shown that individuals with superior performance on tasks designed to measure ANS acuity also demonstrate more advanced mathematical abilities (Halberda, Ly, Wilmer, Naiman, & Germine, 2012;Halberda, Mazzocco, & Feigenson, 2008;Libertus, Feigenson, & Halberda, 2011;Libertus, Odic, & Halberda, 2012;Mazzocco, Feigenson, & Halberda, 2011a;Piazza et al, 2010, Piazza, Pica, Izard, Spelke, & Dehaene, 2013see Chen & Li, 2014 for a meta-analysis). This link has generated a great deal of interest from cognitive psychologists and education researchers, yet there are also many published studies which have failed to demonstrate this correlation (see De Smedt, Noël, Gilmore, & Ansari, 2013, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies reported the existence of a relationship between arithmetic performance or math ability, and the value of the Weber fraction, both in children (e.g., Libertus, Feigenson, & Halberda, 2011;Inglis, Attridge, Batchelor, & Gilmore, 2011, experiment 1) and in adults (e.g., DeWind & Brannon, 2012;Guillaume, Nys, Mussolin, & Content, 2013;Halberda, Ly, Wilmer, Naiman, & Germine, 2012;Libertus, Odic, & Halberda, 2012;Nys & Content, 2012;Nys, Ventura, Fernandes, Querido, Leybaert, & Content, 2013). Notwithstanding these positive findings, contradictory results were also reported, with several studies failing to observe any significant correlation between ANS acuity (computed from such comparison tasks) and arithmetic competence in children Sasanguie, Göbel, Moll, Smets, Reynvoet, 2013;see also De Smedt, Noël, Gilmore, & Ansari, 2013, for a short review) or in adults (e.g., Castronovo & Göbel, 2012, experiment 1;Inglis et al, 2011, experiment 2;Price, Palmer, Battista, & Ansari, 2012).…”
mentioning
confidence: 99%